PENDIDIKAN DAN SOSIALISASI PERATURAN DAERAH RENCANA INDUK PEMBANGUNAN KEPARIWISATAAN NIAS SELATAN UNTUK MENINGKATKAN PARTISIPASI MASYARAKAT DESA BAWÖNAHÖNÖ DALAM SEKTOR PARIWISATA SEBAGAI KEARIFAN LOKAL BUDAYA NIAS SELATAN - Dakhi, Agustin Sukses (Universitas Nias Raya, 2024)
This community service activity aims to provide education and socialization regarding the Regional Regulation of the Master Plan for Tourism Development to the community of Bawönahönö Village, Fanayama District, South Nias Regency. The purpose of this socialization is to enhance the community's understanding of the importance of regulations in managing tourism based on the local wisdom and culture of South Nias. The method used in this activity involves presenting material followed by a question-and-answer session, where participants, consisting of the village head, customary leaders, religious leaders, youth, and local community members, were given the opportunity to discuss the existing regulations and their roles in the development of the tourism sector. The results of this activity indicate that the community is increasingly aware of the importance of regional regulations in creating sustainable tourist destinations. Additionally, there was an agreement to engage the community more actively in the preservation of culture and management of tourist attractions. Therefore, this activity is expected to strengthen community participation in tourism development and preserve the local culture of South Nias.